Un média est-il une marque ? - Valérie Patrin-Leclère (Communication)
The author sets out to correct a misconception : media are, or have become, brand names. Years of observations and analyses have led her to raise key questions as to the complexity of the recent media transformations and of their ensuing changing public images. Behind the everyday use of the brand word are hidden tense professional practices, a difficult economic environment, and a sociocultural reconfiguration of the public sphere. The question of brand names is political in nature.